Long-Term Report of a Comprehensive Molecular and Genomic Analysis in NRG Oncology/RTOG 0424: A Phase II Study of Radiation and Temozolomide in High-Risk Grade II Glioma. (2021) - Fleming, Jessica L.; Pugh, Stephanie L.; Fisher, Barbara J.; Lesser, Glenn J.; Macdonald, David R.; Bell, Erica H.; McElroy, Joseph P.; Becker, Aline P.; Timmers, Cynthia D.; Aldape, Kenneth D.; Rogers, C. Leland; Doyle, Thomas J.; et al.
Abstract : PURPOSE: This study sought to determine the prognostic significance of the WHO-defined glioma molecular subgroups along with additional alterations, including MGMT promoter methylation and mutations in ATRX, CIC, FUBP1, TERT, and TP53, in NRG/RTOG 0424 using long-term follow-up data. METHODS: Mutations were determined using an Ion Torrent sequencing panel. 1p/19q co-deletion and MGMT promoter methylation were determined by Affymetrix OncoScan and Illumina 450K arrays. Progression-free survival (PFS) and overall survival (OS) were estimated using the Kaplan-Meier method and tested using the log-rank test. Hazard ratios were calculated using the Cox proportional hazard model. Multivariable analyses (MVAs) included patient pretreatment characteristics. RESULTS: We obtained complete molecular data to categorize 80/129 eligible patients within the WHO subgroups. Of these, 26 (32.5%) were IDH mutant/co-deleted, 28 (35%) were IDH mutant/non-co-deleted, and 26 (32.5%) were IDH wild-type. Upon single-marker MVA, both IDH mutant subgroups were associated with significantly better OS and PFS ( P values < .001), compared with the IDH wild-type subgroup. MGMT promoter methylation was obtained on 76 patients, where 58 (76%) were methylated and 18 (24%) were unmethylated. Single-marker MVAs demonstrated that MGMT promoter methylation was statistically significant for OS ( P value < .001) and PFS ( P value = .003). In a multimarker MVA, one WHO subgroup comparison ( IDH mutant/co-deleted v IDH wild-type) was significant for OS ( P value = .045), whereas MGMT methylation did not retain significance. CONCLUSION: This study reports the long-term prognostic effect of the WHO molecular subgroups, MGMT promoter methylation, and other mutations in NRG/RTOG 0424. These results demonstrate that the WHO molecular classification and MGMT both serve as strong prognostic indicators, but that MGMT does not appear to add statistically significant prognostic value to the WHO subgrouping, above and beyond IDH and 1p/19q status.